Challenges in teaching Islamic education and requirements of the development of Islamic cognitive domains - Zulkifli, Hafizhah; Ismail, Ahmad Munawar; Muhamad, Nurul Asiah Fasehah; Hussin, Nur Hanani; Zamri, Hifdzi Zaim (Institute of Advanced Engineering and Science, 2025)
Bloom taxonomy that has long been used in Islamic education is no longer adequate to achieve the goal of Islamic education. The exploration of cognitive domain in the perspective Islamic education needs to be explored so that it can be used as a reference in enhancing the quality of teaching and assessments. This research aims to understand the challenges faced by teachers in Islamic education and to explore the need to develop Islamic cognitive domains. A qualitative method of research is applied by conducting a semi structured interview with four informants with teaching experience between 20 to 32 years of teaching Islamic education. The findings show that seven theme challenges in teaching and learning Islamic education, for instance, lack of adab (values), not appropriate for Islamic culture, Bloom’s taxonomy not equivalent to the curriculum document standard and assessment, deficiency in understanding lesson content, time constraints, deficiency of professional judgement skills, and lack of continuous assessment. There is need to construct a taxonomy in Islamic education with these cognitive elements to be considered as elements in the taxonomy which are internalizing, analysis, gratefulness, habituation, sincerity, implementing, consistency, and reflecting.